Nord-Grönland: Die Forschungen der Britischen Nordgrönland-expedition 1952-1954 - Georgi, Johannes (ERDKUNDE, 1958)
Based on the report, North Ice (London, 1957) by the leader of the expedition, Commander C. J. W. Simpson (RN), and the scientific reports so far published, an account is given of the course of this expedition, which is a worthy successor to those of Nansen, Watkins, Alfred Wegener and P. E. Victor, and which has opened up for the first time the northern section of this gigantic ice sheet in glaciological and meteorological respects. There, in the winter station North Ice, investigations were carried out for two years similar to those previously conducted further south in Eismitte in 1930/31 and 1949/51. Across the whole of Greenland along 78° N a gravity profile was laid. The seismic measurements of the thickness of the ice became an important geophysical rarity due to the phenomenon of the lack of a reflexion over extensive areas. Here in the northern section the rock bottom in the centre of Greenland is also partly below sea level, as the French measurements further south have similarly shown. These investigations, as well as the exploration and the mapping of Dronning Louise Land near the east coast, demanded gigantic transport achievements, which are appreciated in detail, and which taxed physical strength and the morale of all members, including the R. A. F., to the limit. In the second part of this paper - in respect of a possible German edition of the expedition report - suggestions are made for the completion and correction of the enclosed maps and further an account is given of the explorations in Dronning Louise Land since the Danmark expedition, 1906/08. It may be that some of the scientific problems could have been more successfully tackled if more consideration had been given to earlier work. As an appendix to the paper there follows a list of the place names of eastern Greenland as used by the Second German North Polar Expedition (1869/70) under Captain Koldewey.